Influence of two formulation types and moisture levels on the storage stability and insecticidal activity of Beauveria bassiana. Issue 5 (4th May 2019) - Lopes, Rogerio Biaggioni; Faria, Marcos
ABSTRACT: The formulation of mycopesticides may require a physical separation of conidia from the substrate and subsequent drying. In the present study, Beauveria bassiana conidia produced by solid-state fermentation were harvested either through a dry or washing protocol. Washed conidia were used to design a water-dispersible granule (WG) formulation, whereas sieved conidia were mixed with an emulsifiable oil to achieve an oil-based formulation (OD). Potential harmful effects caused by the formulation type on the storage stability and insecticidal activity against Hypothenemus hampei were assessed. As expected, the time for initial conidial germination to drop 50% (GT50 ) in all treatments was deeply influenced by storage temperatures, which varied from over 180 days at 4 °C to less than 90 days at 35°C. In all four tested temperatures, GT50 s for unformulated dry conidia were significantly higher than for those formulated as WG, and the latter was similar to conidia formulated as OD in the two highest temperatures. Residual water content in the OD formulation (1, 600 vs. 340 ppm) had a negative influence on conidial survival under storage, whereas WG granules immediately dried after the washing protocol showed conidial germination similar to granules exposed to a slower dehydration regime. Mortality of H. hampei adults exposed to different concentrations of B. bassiana formulated as WG was slightly lower (10–15%) than either the OD or the unformulated conidia. In brief, we have demonstrated that formulation type and their moisture level can affect the storage stability and insecticidal activity of B. bassiana conidia toward the coffee berry borer. Of particular importance, we have shown that drying oils prior to formulation could improve the storage of mycopesticides, an approach that may find industrial applications.